2022
DOI: 10.3389/fpsyg.2022.871391
|View full text |Cite
|
Sign up to set email alerts
|

Olfaction and Executive Cognitive Performance: A Systematic Review

Abstract: Objective tests of olfaction are widely available to aid in the assessment of olfaction. Their clearest role is in the characterization of olfactory changes, either reported by or suspected in a patient. There is a rapidly growing literature concerned with the association of olfactory changes with certain neuropsychiatric conditions and the use of olfactory testing to supplement conventional assessments in clinical and research practice is evolving. Neural pathways important for olfactory processing overlap ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 112 publications
0
4
0
Order By: Relevance
“…However, some studies have shown that SARS-CoV-2 can damage the CNS in different ways including direct infection, viruses entering through blood circulation and neuronal pathways, hypoxic and immune injury, and also binding to the angiotensin-converting enzyme 2 (ACE2) receptor, ultimately producing acute and long-term neurological effects ( 37 ). Furthermore, as the olfaction and cognitive functions share common neurocircuitry in the frontal lobe, the high incidence of anosmia following COVID-19 infection, which is also one of the most common persistent symptoms in post-COVID-19 cases, draws attention to the role of olfactory neuroinflammation in cognitive changes, especially executive function ( 35 , 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies have shown that SARS-CoV-2 can damage the CNS in different ways including direct infection, viruses entering through blood circulation and neuronal pathways, hypoxic and immune injury, and also binding to the angiotensin-converting enzyme 2 (ACE2) receptor, ultimately producing acute and long-term neurological effects ( 37 ). Furthermore, as the olfaction and cognitive functions share common neurocircuitry in the frontal lobe, the high incidence of anosmia following COVID-19 infection, which is also one of the most common persistent symptoms in post-COVID-19 cases, draws attention to the role of olfactory neuroinflammation in cognitive changes, especially executive function ( 35 , 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…There are many studies which have examined the general relationship between olfaction and cognition with the majority showing that olfactory performance tends to have significant associations with measurements of frontal lobe executive function ( Westervelt et al, 2005 ; Challakere Ramaswamy and Schofield, 2022 ; Mattos et al, 2022 ). There are a variety of medical conditions in which there is evidence for a positive association between olfactory performance and cognitive functioning.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of practical applications, as we have discussed elsewhere, moving from the findings from group studies of olfaction and its correlates to considering the potential benefits of OI testing of individuals raises many questions and challenges (Ramaswamy and Schofield, 2022). The clearest benefit of OI is to detect olfactory impairments that would confer risk from failure to detect hazards such as smoke or spoiled food.…”
Section: Discussionmentioning
confidence: 99%
“…Olfactory dysfunction (OD) is commonly observed in certain neurodegenerative diseases and may occur in the context of neuropsychiatric disorders such as schizophrenia, depression and panic disorder (Ryo et al, 2017;Fóz et al, 2022). Neural pathways for olfactory processing overlap with those important for aspects of executive functioning concentrated in the frontal lobe, and tests of executive function and olfaction have been shown to positively correlate across a broad array of measures, as recently reviewed (Ramaswamy and Schofield, 2022). Indeed, some investigators have suggested that olfactory tests could serve as a rapid screen for cognitive impairment (Jung et al, 2019;Vance et al, 2023).…”
Section: Introductionmentioning
confidence: 99%